Underwater endoscopic mucosal resection of large colorectal lesions - Uedo, Noriya; Nemeth, Artur; Johansson, Gabriele Wurm; Toth, Ervin; Thorlacius, Henrik (Endoscopy, 2015)
In this prospective study, 11 consecutive patients with neoplastic colorectal lesions (median size 20 mm, range 15 – 25 mm) underwent endoscopic polyp removal by underwater endoscopic mucosal resection (EMR). Six lesions were removed en bloc and five lesions were removed by piecemeal resection. Pathological examination revealed seven R0 resections, and in four cases the pathology could not be determined. Two cases of procedure-related bleeding occurred but these were easily managed using hemostatic forceps and clip application. No perforations or delayed bleedings were observed. Underwater EMR is a relatively simple, safe, and useful method for the removal of large colorectal lesions.